Spawning and nesting behaviour of Tachypleus gigas along the East coast of Peninsular Malaysia - Kassim, Zaleha; John, Akbar; Hadnan, Nur Erni Atika; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal (Canadian Center of Science and Education, 2012)
Present study was aimed to address the spawning and nesting behaviour of Malaysian horseshoe crab (Tachypleus gigas) in observed nesting grounds of East coast of Peninsular Malaysia during monsoonal period. Field sampling was carried out in every full and new moon days between September and December 2009 in Balok (Lat3°56.194’ N, Long103°22.608’ E) and Pekan (Lat3°36.181’ N, Long103°23.946’ E) nesting grounds. A total of 26 nests were found throughout the sampling period (Balok = 4 nests [~15%]; Pekan = 22 nests [~85%]) with higher percentage nesting was noted in November (N = 11 nests [~50%]) in Pekan. No nests were found in Balok station in all sampling months except during September (4 nests). It was also noted that the horseshoe crab preferred nesting during full moon time compared to new moon period. Mean depth × width of the T.gigas nests were 19.96±5.6×10.72±2.1cm. Number of eggs and larval counting in each nest were also recorded together with hydrographic and sedimentological parameters of the nesting grounds. This study clearly showed negative influence of monsoonal cycle on the nest preference and spawning behaviour of T.gigas. Long term monitoring studies would enable us to understand the number of shore reaching horseshoe crabs which is an essential source for the wild population